Empowering Thalassemia Patients and Family to Increase Public Knowledge on Thalassemia - Peter Asa; Danti Nur Indiastuti; Mia Ratwita Andarsini; Jihan Nur Fauziah; Annette d'Arqom (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2021)
Thalassemia, the fifth-most catastrophic disease with 10,555 patients, causes physical, emotional, and economic burden for the patient, their family, and the country. Annually, IDR 500 billion are needed to cover the treatment of thalassemia. This projected number will continue to increase if no action is taken, so education and knowledge dissemination are important for thalassemia prevention. This community development involves thalassemia patients and families as partners and encourages them to share their knowledge and experience about thalassemia with the Indonesian late adolescents, young adult, and middle-aged adult population through an online webinar to increase public knowledge on thalassemia. Education media, such as posters and videos, were developed and disseminated during the activity, followed by live sharing from thalassemia patients, parents, and pediatricians. The respondents’ knowledge of thalassemia was measured using an 11-items questionnaire before and after the online educational activity. The results show that the respondents have a good knowledge of thalassemia, and it increases after attending online education event about the disease (9.74+2.4, 10.22+0.77, p<0.001). Their knowledge was associated with health-related field experience, knowing someone with thalassemia, and their willingness to undergo thalassemia testing (p<0.046, 0.013, and 0.007, respectively). Thus, these findings support the importance of education and dissemination of information regarding Thalassemia. Moreover, strong knowledge might lead to a willingness to undergo thalassemia testing, which might lead to less marriage between carriers and, eventually, a reduction in the incidence of thalassemia major.